School-based smoking prevention strategies for adolescents in a conservative LMIC context: a qualitative study from Egypt - Ba-Break, Maryam; Bewick, Bridgette M.; Elsey, Helen; Huss, Reinhard; Ensor, Tim; Saleh, Mohamed; Donnelly, Sean; Osman, Doaa Mohamed (Frontiers in Public Health, 2025)
ObjectiveAdolescent smoking is a critical form of psychoactive substance misuse, particularly in low- and middle-income countries like Egypt, where youth tobacco use remains a public health concern. This study explored current and potential school-based smoking prevention interventions in a conservative low- and middle-income country context, to identify strategies which enhance adolescents’ capability, opportunity, and motivation to avoid smoking initiation.MethodsA qualitative study was conducted in three public preparatory schools (boys’, girls’, and mixed gender) in Asyut, Upper Egypt. Data was collected through 40 semi-structured interviews with school staff, 16 focus group discussions with 76 pupils (aged 12–13), and analysis of 172 school documents. Creative tools including picture-elicitation and story-making were used with pupils. Data was analysed using the framework approach, guided by the Capability-Opportunity-Motivation-Behaviour model.ResultsSeven meta-themes were identified. Key strategies included educating pupils on the broad consequences of smoking, including health, appearance, fitness, finances, relationships, addiction, religious values, and equipping them with refusal and coping skills. Interventions should promote smoke-free school and home environments, model non-smoking behaviour, and leverage peer influence. Motivational strategies such as storytelling, real-life examples, reward schemes, and accessible extracurricular alternatives were also emphasised. Barriers included limited resources, cultural taboos, and misinformation around e-cigarettes.ConclusionSchool-based smoking prevention interventions in low- and middle-income country settings must be proactive rather than reactive, multi-dimensional and culturally appropriate. Applying the Capability-Opportunity-Motivation-Behaviour model can help schools design integrated interventions that build psychological capability, reshape opportunities, and strengthen both reflective and automatic motivation in early adolescence. The findings have direct implications for public health practice, school policy, and substance misuse prevention programming in resource-constrained and socially conservative settings.